Effects of drought and flooding on beans (Phaseolus vulgaris L.) and groundnut (Arachis hypogaea L.): a comparison - Erhenhi, AH (Bangladesh Journal of Scientific and Industrial Research, 2020)
Effects of drought and flooding on bean (Phaseolus vulgaris L.) and groundnut (Arachis hypogaea L.) were carried out and compared. Plant growth parameters, biomass content, chlorophyll, ash and soil metal content were studied. The result showed that bean was 21.3cm, 21.8cm and 21.1cm for control, drought and flooding while groundnut recorded 19.9cm, 102.3cm and 18.6cm for control, drought and flooding respectively. Biomass composition recorded little or no variation in fresh weight of stem in bean while groundnut varies from 4.77g – 5.05g accordingly. Leaf recorded highest value of fresh weight to be 6.44g recorded in bean cultivated in drought soil with the least recorded to be 3.61 in the control and flooded soil for groundnut plant. The result of the study showed that drought and flooding had relatively positive effects on the growth properties of bean and groundnut as both plants were able to germinate and grow under both conditions. Bangladesh J. Sci. Ind. Res.55(3), 189-196, 2020